Developing Long-Term Finance in Emerging Markets : Using Bank Debentures - Lessons from Japan - Watanabe, Masakazu (World Bank, Washington, DC, 2012)
From the early 1950s until quite recently, the Japanese government took an active role in promoting a bank debenture market. This Note explains how the Japanese bank debenture market developed and what role these debentures played in establishing a bond market. The debenture market started life at a time when massive amounts of long-term capital were needed for reconstruction. Capital markets had not yet developed, and market-base long-term funding was seen as too risky by both investors and financial institutions.